The generative development of traditional and self-completing (restricted branching) cultivars of white lupin (Lupinus albus L.), yellow lupin (L.luteus L.) and narrow-lafed lupin (L. angustifolius L.) grown under different phytotron conditions - Frankowski, Kamil; Wilmowicz, Emilia; Kućko, Agata; Mączkowski, Rafał; Marciniak, Katarzyna; Kopcewicz, Jan (Plant Breeding and Seed Science, 2014)
Increasing the number of flowers and pods set, as well as reducing the intensity of their abortion, is of crucial importance for the yielding of leguminous plants. This study examined the effects of the type of soil used and mineral fertilization applied on the generative development of the traditional and self-completing (restricted branching) cultivars of white lupin (Lupinus albus L.), yellow lupin (L. luteus L.) and narrow-lafed lupin (L. angustifolius L.) cultivated under controlled phytotron conditions. Experiments carried out under such conditions allow for the elimination of variable environmental factors affecting the course of plant ontogenesis in field cultivation, and enable unambiguous interpretation of the biochemical and molecular influence of a selected factor on the physiological process studied. For the first time, the influence of different cultivation factors on generative development of traditional and selfcompleting (restricted branching) cultivars of lupins under phytotrone was examined. The research results presented here indicate that each of the selected lupin cultivars has its own characteristic cultivation conditions that are optimal for its generative development. The largest number of flowers were formed by the traditional cultivars of L. luteus and L. angustifolius, as well as the self-completing (restricted branching) cultivars of L. luteus and L. albus grown in class IIIa soil material. The lowest flower abortion rate was observed in L. albus grown in class V soil material, in L. luteus grown in class IIIa soil material, and in L. angustifolius grown in class Iva soil material. Regardless of the cultivation conditions applied, in all of the lupin cultivars examined the first pods to be set were characterized by the lowest abortion rate. The results obtained allowed for the development of lupin phytotron cultivation models for the purposes of research on generative development control.